Framing a strategic approach for reserve component joint officer management - Thie, Harry; Harrell, Margaret C.; Kirby, Sheila Nataraj, 1946-; Crego, Al.; Yardley, Roland J.; Nagda, Sonia; National Defense Research Institute (U.S.). Forces and Resources Policy Center; Rand Corporation; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 2006)
This research frames a strategic approach to reserve joint officer management that addresses the requirements for, and the supply of, joint officers in the reserve component, and also accounts for the unique constraints and challenges involved in joint officer management for reserve active-status list officers. Because the work required of many reservists is becoming increasingly joint, the need for a systematic examination of how reserve active-status list officers are trained and developed in joint matters is becoming more and more urgent-especially given the dramatic increase in the use of the reserve forces. A strategic approach to joint officer management for reserve active-status list officers must assess the need for officers with prior joint knowledge, experience, and acculturation in certain positions as well as their availability. The authors estimate the supply of joint reserve officers and make several recommendations to help implement a strategic approach to reserve component joint officer management.
Introduction -- Developing and managing officers in the active and reserve components -- A strategic approach to joint officer management: why and how -- Determining demand for reserve active-status list officers with prior joint education and/or experience -- Determining potential supply of reserve active-status list joint officers -- Conclusions and recommendations -- Availability of current data to support reserve component joint officer management -- Theory behind training and experience evaluation methods.
"RAND National Defense Research Institute."
"This research was conducted within the Forces and Resources Policy Center of RAND's National Defense Research Institute"--Pg. IV.
Includes bibliographical references (p. 115-118).
Also available on the internet via WWW in PDF format.
Keywords: Military education -- United States; Unified operations (Military science); United States -- Armed Forces -- Officers -- Management; United States -- Armed Forces -- Officers -- Training of; United States -- Armed Forces -- Reserves -- Management